13C NMR Investigation of Some New Azodiamines - Nanjan, M.J.; Rajendiran, T.V. (Asian Journal of Chemistry, 2010)
Three new organic compounds viz., 2,2'-dimethyl-4,4'- diaminoazobenzene, 2,2'-dichloro-4,4'-diaminoazobenzene and 2,2'-dimethoxy-4,4'-diaminoazobenzene have been synthesised and their structures confirmed by 1H and 13C NMR data with selective 13C-1H decoupling along with other spectral data. The chemical shifts of C-1 to C-6 carbons of the phenyl group were correlated with the substituent effects.